Does a learning curve exist for accuracy in three-dimensional planning for maxillary positioning in bimaxillary orthognathic surgery?. Issue 6 (June 2020) - Antonini, F.; Borba, A.M.; Pagnoncelli, R.M.; Han, M.; Markiewicz, M.R.; Miloro, M.
Abstract: The purpose of this study was to investigate the influence of time, and experience, on the accuracy of maxillary repositioning in bimaxillary orthognathic surgery performed using virtual surgical planning (VSP). Patients who had undergone bimaxillary orthognathic surgery were reviewed. Maxillary position on pre- and postoperative computed tomography scans was compared. The patients were divided into groups according to the year in which VSP was performed and surgery completed. Linear distances between upper jaw reference landmarks were measured in all three planes of space to determine accuracy between the preoperative VSP and the surgical outcome at various time points. One hundred subjects met the eligibility criteria for assessment and were allocated to groups: 2013 ( n = 10), 2014 ( n = 17), 2015 ( n = 39), 2016 ( n = 20), and 2017 ( n = 14). Overall, the results demonstrated improved precision in maxillary position over the years, with more accurate results in patients who underwent surgery in 2015, 2016, and 2017. Mean linear differences between planned and obtained results demonstrated more accurate results in the horizontal direction, followed by transverse and vertical directions. An overall average difference within 1 mm was observed for 51.3% of the measurements included in the sample group. Time, and surgeon experience, can influence the accuracy of maxillary positioning in bimaxillary orthognathic surgery.